Crop diversity benefits carabid and pollinator communities in landscapes with semi‐natural habitats. Issue 11 (12th August 2020) - Aguilera, Guillermo; Roslin, Tomas; Miller, Kirsten; Tamburini, Giovanni; Birkhofer, Klaus; Caballero‐Lopez, Berta; Lindström, Sandra Ann‐Marie; Öckinger, Erik; Rundlöf, Maj; Rusch, Adrien; Smith, Henrik G.; Bommarco, Riccardo
Abstract: In agricultural landscapes, arthropods provide essential ecosystem services such as biological pest control and pollination. Intensified crop management practices and homogenization of landscapes have led to declines among such organisms. Semi‐natural habitats, associated with high numbers of these organisms, are increasingly lost from agricultural landscapes but diversification by increasing crop diversity has been proposed as a way to reverse observed arthropod declines and thus restore ecosystem services. However, whether or not an increase in the diversity of crop types within a landscape promotes diversity and abundances of pollinating and predaceous arthropods, and how semi‐natural habitats might modify this relationship, are not well understood. To test how crop diversity and the proportion of semi‐natural habitats within a landscape are related to the diversity and abundance of beneficial arthropod communities, we collected primary data from seven studies focusing on natural enemies (carabids and spiders) and pollinators (bees and hoverflies) from 154 crop fields in Southern Sweden between 2007 and 2017. Crop diversity within a 1‐km radius around each field was positively related to the Shannon diversity index of carabid and pollinator communities in landscapes rich in semi‐natural habitats. Abundances were mainly affected by the proportion of semi‐natural habitats in the landscape, with decreasing carabid and increasing pollinator numbers as the proportion of this habitat type increased. Spiders showed no response to either crop diversity or the proportion of semi‐natural habitats. Synthesis and applications . We show that the joint effort of preserving semi‐natural habitats and promoting crop diversity in agricultural landscapes is necessary to enhance communities of natural enemies and pollinators. Our results suggest that increasing the diversity of crop types can contribute to the conservation of service‐providing arthropod communities, particularly if the diversification of crops targets complex landscapes with a high proportion of semi‐natural habitats. Abstract : We show that the joint effort of preserving semi‐natural habitats and promoting crop diversity in agricultural landscapes is necessary to enhance communities of natural enemies and pollinators. Our results suggest that increasing the diversity of crop types can contribute to the conservation of service‐providing arthropod communities, particularly if the diversification of crops targets complex landscapes with a high proportion of semi‐natural habitats.